Personality profile and affective state of patients with inflammatory bowel disease. Issue 5 (May 1989) - Robertson, D A; Ray, J; Diamond, I; Edwards, J G
Abstract : The Eysenck Personality Inventory and Hospital Anxiety and Depression scale were administered to 80 patients undergoing medical treatment for long standing inflammatory bowel disease: 22 patients were studied before the diagnosis was established and 40 patients with diabetes mellitus served as controls. High neuroticism and introversion scores were more prevalent in the patients with inflammatory bowel disease than controls (p less than 0.05) and these characteristics were as prominent in patients before diagnosis as in established cases. Introversion scores increased with the duration of disease (r = 0.51). Depression was uncommon, occurring only in patients with active chronic disease. Patients believed there was a close link between personality, stress and disease activity. Fifty six of the patients recognised factors that initiated the disease and in 42 this was thought to be a stressful life event or a 'nervous personality'.